Life during the covid-19 pandemic of the poorest families in a Philippine municipality - Mark Jason Dungog; John Wayne V. Jacinto (Penerbit Universiti Kebangsaan Malaysia, 2023)
The COVID-19 pandemic has affected various sectors of society and people of all socioeconomic backgrounds, and each either faces economic, social, or psychological challenges. However, it is interesting to examine how the poorest of the poor families who faced limitations in their socioeconomic conditions lived and were affected during the pandemic. By employing the descriptive phenomenological inquiry, this study aimed to explore and describe the meaning of the experiences of the Pantawid Pamilya Pilipino Program (4P’s) beneficiaries, particularly the 4P’s level 1 families in Bonifacio, Misamis Occidental, Philippines amidst the COVID-19 pandemic. Six participants were purposively chosen for the study. The semi-structured interview was guided by the central question: what is the meaning of your situation now living with the COVID-19 pandemic? The findings of the study revealed five central themes which represented the participants' experiences amidst the COVID-19 pandemic, namely, socioeconomic limitations and struggles, acceptance of the existing condition, interdependence within social networks, fear and disbelief over the disease, and optimistic outlook on their condition.